2019
DOI: 10.1177/0300060519857839
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of IGF-1 against myocardial ischemia/reperfusion injury through activation of PI3K/Akt pathway in rats in vivo

Abstract: Objective It remains unknown whether insulin-like growth factor-1 (IGF-1) can attenuate myocardial ischemia/reperfusion (I/R) injury in vivo by activating the phosphoinositide 3-kinase/protein kinase B (PI3K/Akt) pathway. This study investigated the possible interaction of IGF-1 with the PI3K/Akt pathway in cardioprotection against in vivo myocardial I/R injury in rats. Methods We established a myocardial I/R model in rats through left anterior descending artery ligation for 40 minutes followed by 6 hours repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…This pathological scenario is related to the observed reduction of pAkt/Akt ratio in OG. After IGF-1 therapy apoptosis levels were reduced in OG þ IGF-1 through PI3K/ Akt pathway upregulation, which has anti-apoptotic effect in cardiomyocytes [26], corroborating data of Liao et al (2019) [27], which showed that IGF-1 can protect ischemic myocardium from ischemia/reperfusion injury by activating the PI3K/Akt pathway in vivo. Previous work demonstrated that mice lacking both insulin and IGF-1receptors in the heart displayed disrupted PI3K and Akt activity in cardiomyocytes, which contributed to cardiac failure and animal death [28].…”
Section: Discussionsupporting
confidence: 84%
“…This pathological scenario is related to the observed reduction of pAkt/Akt ratio in OG. After IGF-1 therapy apoptosis levels were reduced in OG þ IGF-1 through PI3K/ Akt pathway upregulation, which has anti-apoptotic effect in cardiomyocytes [26], corroborating data of Liao et al (2019) [27], which showed that IGF-1 can protect ischemic myocardium from ischemia/reperfusion injury by activating the PI3K/Akt pathway in vivo. Previous work demonstrated that mice lacking both insulin and IGF-1receptors in the heart displayed disrupted PI3K and Akt activity in cardiomyocytes, which contributed to cardiac failure and animal death [28].…”
Section: Discussionsupporting
confidence: 84%
“…The PI3K/Akt signaling pathway is a conserved pathway to many aspects of cell growth and survival, in physiological as well as in pathological conditions 20 , 21 . Recent studies have identified that PI3K/Akt is crucial for limiting oxidative stress, proinflammatory, and apoptotic events in response to I/R stimuli 22 24 . It has been well documented that activation of PI3K/Akt is associated with decreased myocardial ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as a serine/threonine kinase, Akt alone mediates many different effects including cardioprotection, carcinogenesis, regulation of metabolism, expression of ABC transporters or vimentin via more than one hundred downstream effector molecules [ 54 , 55 , 56 , 57 ]. According to the literature, taxifolin can mediate Akt dephosphorylation that directly contributes to depletion of vimentin [ 57 , 58 ] as confirmed by experiments with the Akt inhibitor GSK690693 ( Appendix A , Figure A4 ).…”
Section: Discussionmentioning
confidence: 99%